LEARNING RESULTS OF MUHAMMADIYAH 2 GEMOLONG HIGH SCHOOL STUDENTS SRAGEN DISTRICT - Sumarni, Ninik; Mursito, Bambang; Sakidi (International Journal of Research -GRANTHAALAYAH, 2024)
A student’s observable and quantifiable abilities, including their knowledge, attitudes, and skills, are known as learning outcomes. Learning motivation, study interest, learning style, and self-efficacy are some of the internal and environmental elements that impact learning outcomes. The objective of this research is to get a better understanding of how factors such as students’ self-efficacy, learning style, study interest, and motivation affect their academic performance at SMA Muhammadiyah 2 Gemolong in Sragen. This study employs a quantitative descriptive approach. There are a total of 398 students enrolled in this study, with 99 serving as a representative sample from the population of SMA Muhammadiyah 2 Gemolong in Sragen. Observation, surveys, interviews, recording, and citations to relevant studies are all part of the data gathering process. The method for analyzing the data makes use of traditional tests for assumptions and hypothesis testing. The t-test, multiple regressions, and coefficient determinations are all tools used in hypothesis testing. This study found that students’ levels of motivation significantly impacted their performance in the classroom at SMA Muhammadiyah 2 Gemolong in Sragen. Students’ levels of interest do not affect their performance in class at SMA Muhammadiyah 2 Gemolong in Sragen. Students’ learning results at SMA Muhammadiyah 2 Gemolong, Sragen are positively impacted by learning style characteristics. Students at SMA Muhammadiyah 2 Gemolong in Sragen have high levels of self-efficacy, which positively affects their academic performance.